Exploring the psychosocial impacts of the 2015 Aliso Canyon natural gas blowout: Tracing an ‘invisible’ disaster through a novel Disaster Invisibility Framework - Lynch, Kathleen A.; Loeb, Tamra; Gravereaux, Charles; Monte-Sano, Sydney; Hoang, Anh; Batteate, Christina; Liu, Honghu; Abramson, David M.; Eisenman, David P. (Social science & medicine (1982), 2025)
Between October 2015–February 2016, the Aliso Canyon gas well in Los Angeles County leaked more than 100,000 metric tons of methane and ethane gas into the atmosphere, the largest uncontrolled release from a single underground gas storage facility in United States history. This event was an ‘invisible disaster’ both in terms of the physical nature of exposure (aerosolized natural gas) and collective recognition. This qualitative study aimed to identify and articulate the multiple ‘invisible’ dimensions of the Aliso Canyon blowout as a framework for understanding the disaster's long-term psychological, social, and community impacts. Using a purposive, age-stratified sampling approach, we conducted six virtual focus groups in spring 2024 with young (18–34), middle-aged (35–64), and older adult (65+) residents living within a 5-mile radius of the gas leak wellhead. Transcripts were inductively coded using the Framework Method. Thematic analysis identified four dimensions of disaster invisibility: 1) Invisible Risks: delayed and conflicting communication left participants to assess and manage their own risk. 2) Invisible Harms: unknown toxic exposure levels facilitated health anxiety. 3) Invisible Community: persistent anger at a lack of corporate accountability and government response to concerns. 4) Invisible Changes: a loss of comfort, safety, and altered life plans, exacerbated by uncertain future health status. The Disaster Invisibility Framework is a novel approach to assessing psychological, social, and community impacts following disaster exposure. The themes reported in this paper underscore that addressing invisibility should be a key component of future efforts to support disaster recovery. •2015 Aliso Canyon gas well blowout harmed long-term mental health and well-being.•Community focus groups define key disaster characteristic: Invisibility.•Invisibility Framework is a novel way to assess the psychosocial harms of exposure.